Myopia prevalence, refractive status and uncorrected myopia among primary and secondary school students in Germany - Astrid Hönekopp; Lisa-Marie Tommes; Philipp Doebler; Sarah Weigelt (Frontiers in Medicine)
IntroductionThe increasing prevalence of myopia worldwide is problematic because myopia can result in severe secondary pathologies, and is associated with considerable financial burden. With plenty of prevalence data available for some regions, current data for Europe remain sparse. Yet, information on myopia prevalence and associations is essential for monitoring, preventive and interventive purposes. Likewise, uncorrected refractive errors are also critical, as they can, e.g., affect educational outcomes, making information on uncorrected myopia valuable for diagnostics and health education.MethodsWe performed non-cycloplegic autorefraction on two samples in Germany. The younger sample included 489 primary school students (grades 3–4, mean age: 9.30 ± 0.78 years), the older sample 1,032 secondary school students (grades 8–10, mean age 14.99 ± 1.12 years). These samples mark the limits of the age range during which school myopia usually emerges.ResultsMyopia (spherical equivalent ≤ −0.75D) prevalence was 8.4% in the younger sample and 19.5% in the older sample. The prevalence was generally higher in higher grade levels, with the most notable difference between grades 8 and 9. Females were more myopic than males in all grades except grade 3, with the largest gender difference in grade 10. The older sample also exhibited a more myopic spherical equivalent than the younger sample. In the older sample, spherical equivalent was more myopic in females than in males, and in grade 9 and 10 participants more than in grade 8 participants. Rates of uncorrected myopia were extremely high: 51.2% in the younger sample and 43.3% in the older sample.DiscussionThe obtained myopia prevalence rates are generally consistent with other European studies, as is the higher prevalence in female than male adolescents, accelerating with age. The high rates of uncorrected myopia warrant further investigation and should inform public health policies, including the implementation of regular refractive screenings.